SOLUBILITY ENHANCEMENT OF RITONAVIR (RTV) BY DIFFERENT SOLID DISPERSION METHODS - KATARIYA VIJAY R (International Journal of Pharma and Bio Sciences, 2013)
The reason for present research works is to exploit solid dispersion technique to improve the solubility and dissolution properties of a poorly water-soluble drug RTV. The solid dispersions were prepared with Kollidon VA 64 by different methods in different ratios. Solid dispersions were prepared by different methods and evaluated for drug content analysis, saturation solubility and dissolution study. Also the optimized ratio of solid dispersion was characterized by different analytical methods like DSC (differential scanning calorimeter), SEM (Scanning electron microscopy), PXRD (Powder X-ray diffraction) and FTIR (Fourier transform infrared spectroscopy) to prove the change in physical form of drug and to prove the complexation between polymer and drug.